A Straightforward Synthesis to Novel 1,10-Phenanthrolines with Fused Thiophene Structure - Tünnermann, Maike; Rehsies, Pia; Flörke, Ulrich; Bauer, Matthias (Synlett, 2018)
We report here a straightforward synthesis for a series of new structures with fused 1,10-phenanthroline-thiophene connection. They are synthesized with a modified Hinsberg thiophene procedure, followed by successive modification to yield several 5,7-disubstituted thieno[3,4-f][1,10]phenanthrolines, most notable thiophene-substituted compounds that could be potentially of use for organic electronics applications. For some selected examples, crystal structures were obtained, showing a nearly coplanar arrangement around the fused connection, also beneficial for an effective electron transfer in organic electronics or solar cells.
Keywords: thiophene; 1,10-phenanthroline; fused thiophene; semiconductor; organic solar cells